A bioassay screening Trichoderma isolates for enhancement of root development in Impatiens walleriana cuttings - Clouston, A.M.; Hill, R.A.; Minchin, R.; Braithwaite, M.; Stewart, A. (New Zealand Plant Protection, 2010)
The potential of 62 Trichoderma spp isolates to enhance root development on cuttings was evaluated in a screening bioassay using the ornamental plant impatiens (Impatiens walleriana) Increased root development and consequent growth of cuttings induced by Trichoderma treatments were compared to that of a commercial rooting hormone (indole3 butryic acid) and untreated cuttings Results recorded after 3 weeks growth indicated sufficient resolution in the bioassay to detect statistical growth differences between treatments As expected treatment with IBA (positive control) enhanced root growth in root score root dry weight and root to shoot ratio parameters assessed across all three screening experiments Six individual Trichoderma isolates and a commercial mixture of isolates were also identified as significantly improving root growth with 2065 increases in the measured growth variables relative to untreated cuttings The bioassay provided an ideal system for measuring rooting response and allowed accelerated screening of Trichoderma candidates useful for enhancing root development of cuttings